Studies in early Jewish epigraphy - Henten, J. W. van.; Horst, Pieter Willem van der. (Arbeiten zur Geschichte des antiken Judentums und des Urchristentums, 1994)
This volume contains the papers of a workshop on Jewish epigraphy in antiquity organized at Utrecht University in 1992. Among the participants were collaborators of the Cambridge Jewish Inscriptions Project and of the Tübinger Atlas des Vorderen Orients project. Important aspects of ancient Jewish inscriptions are highlighted in the papers, like the connection between documentary and literary texts. Several papers focus on aspects of the history of Jewish communities in the diaspora. Specialists in Jewish epigraphy will find surveys of parts of the corpus of Jewish inscriptions (curse inscriptions, metrical epitaphs, alphabet-inscriptions) and discussions of some fixed opinions, and Jewish inscriptions are discussed in a wider literary and historical contexts as well.